Cross-cultural adaptation of the University Student Depression Inventory for Brazil - Fernanda Pâmela Machado; Marcos Hirata Soares (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to adapt the University Student Depression Inventory for Brazil. Methods: we used 6 methodological stages: initial translation, translation synthesis, back-translation, expert committee, pre-final version testing and document submission to the scale authors for assessing the adaptation process. The judges were 2 methodologists, 1 health professional and 2 translators. For the pre-test, 30 undergraduate and graduate students participated. Results: the data were analyzed by Excel®, resulting in satisfactory content validity, a scale composed of 30 items, 3 domains and a total CVC of 0.91. Language clarity and practical relevance had a CVC of 0.91 and theoretical relevance of 0.90. Conclusions: the USDI-BR was cross-culturally adapted for Brazil, showing evidence of satisfactory content validity. After an analysis of reliability and convergent validity to be tested in future studies, multidisciplinary teams will be able to apply this scale to Brazilian students.